ETUDE DE LA QUALITE PHYSICO-CHIMIQUE ET MICROBIOLOGIQUE DE L’EAU DES PUITS DE LA REGION EL HASSIANE (W. Mostaganem) - MERAH, Abdelkader (My University, 2019)
The use of water in the food or hygiene field requires excellent physicochemical and microbiological quality. Drinking water is one of the most controlled food products. It must comply with quality standards. Thus, it must not contain any micro-organism, parasite or substance posing a potential danger to human health; it must meet the requirements of the standards of potability. Our study focuses on the evaluation of the physicochemical and microbiological quality of water from the wells of the municipality of El Hassiane and drinking water (ADE network). At the end of this study, the physicochemical characteristics of well water were determined in the El Hassiane region. Among the parameters measured, we find that they have revealed a neutral pH (between 7.79 and 7.91), a temperature oscillates between 18.5 and 20 ° C with conductivity varies between 1273 and 2830 μs / cm and low nitrite content. Parameters are in line with Algerian standards and those of the WHO World Health Organization guidelines. The microbiological analysis of the tap water showed a total absence of pathogenic germs which allowed us to judge that the water intended for the human consumption of the municipality El Hassiane is of very good quality of sanitary point of view. Thus the results of microbiological analyzes of well water in the Ben Yahi region illustrated a total absence of pathogenic germs. However, the bacteriological results of well water from the Kouara region revealed the presence of total coliforms and the complete absence of faecal contamination indicators such as fecal coliforms and fecal streptococci. Then, it is concluded that the water in this well is of suspect quality and doubtful from the point of view of the presence of total coliforms. It is not suitable for human consumption and requires prior treatment.
Keywords: water; tap water; well water; physico-chemical analyzes; bacteriological analyzes